Divisions of regulatory labor, institutional closure, and structural secrecy in new regulatory states: The case of neglected liquidity risks in market-based banking - Leon Wansleben (Regulation & Governance, 2021)
Monetary policy and financial regulation have been regarded one of the paradigmatic domains where states can reap the benefits of delegating clearly delineated and unequivocal policy tasks to specialized technocrats. This article discusses the negative side-effects and unintended consequences of particular ways to partition such tasks. The separation between monetary policy formulation, central banks' money market management, and financial supervision has weakened policy makers' capacities to address risks associated with banks' active liability management and to mitigate pro-cyclical dynamics in money markets. These adverse effects derive from the neglect of liquidity as a regulatory problem in formal task descriptions; from the obstacles to positive coordination between specialized technocrats in the self-contained domains of monetary policy formulation, implementation, and prudential regulation; and from a dissociation between formal responsibilities, which lie with regulators, and the resources residing in money market divisions – market expertise and influence over counterparties – that are critical to influence bank behavior. I explore these mechanisms with an in-depth case study of British monetary and financial governance between 1970 and 2007. I posit that we can generalize the respective mechanisms to explore unintended effects of `agencification' and to contribute to a broader re-assessment of those organizing principles that have guided the construction of `new regulatory states'.
Keywords: 330; “the new regulatory state”; bureaucratic fragmentation; divisions of expert work; financial governance; liquidity